Awareness of cervical cancer among the undergraduate medical students of Churachandpur Medical College, Manipur, India - Sarda Devi, Okram; Vashum, Melody (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The incidence of cancer overall is in increasing trends all over the world cervical cancer is the only vaccine preventable cancer. India need robust screening and vaccination program and for this the medical students need to understand and learn about it. This study was done to explore knowledge of cervical cancer among the medical undergraduates so that teaching pedagogy can n be plan based on the previous knowledge of the students which will in turn result in providing better health services to our community. Methods: The study was a cross-sectional observational study done at Imphal campus of Churachandpur Medical College on all 183 undergraduates medical graduates for duration of 1 month from May 15th, 2024, to June 15th, 2024. Results: 6 out of 142 students (4%) % of the students have never heard of cancer cervix 10% didn’t know that cancer cervix is preventable, 8% didn’t know that early detection can be done, 24% did not know about cancer cervix screening, 32% have never heard of pap smear 11% have never heard of HPV vaccine 6% did not know that HPV vaccine can prevent cancer cervix and 35% did not know when is HPV vaccine given. Conclusions: Our medical students are still lagging, and we have to work on providing and developing educational programs to improve the knowledge and awareness of cancer cervix.